Airflow limitation in COPD is associated with increased left ventricular wall stress in coincident heart failure. Issue 9 (September 2015) - Alter, Peter; van de Sand, Kirsten; Nell, Christoph; Figiel, Jens H.; Greulich, Timm; Vogelmeier, Claus F.; Koczulla, Andreas R.
Abstract Background COPD and heart failure occur with a considerable coincidence. Beside well-known mechanisms of increased right heart load in COPD, dedicated changes of the left ventricle (LV) are ill-defined and the question remains, whether specific interactions exist beyond common shared risk factors. Methods LV wall stress was calculated based on cardiac magnetic resonance imaging in 28 patients with COPD (GOLD I to III) and coexistent heart failure (LVEF 42 ± 19%) due to non-ischaemic and ischaemic cardiomyopathy. Results LV enddiastolic (p = 0.048) and endsystolic wall stress (p = 0.034) increased from GOLD stage I to III. Reduced FEV1 was correlated with increased enddiastolic (p = 0.0210) and endsystolic LV volume (p = 0.0413) and with increased enddiastolic (p = 0.0161) and endsystolic LV wall stress (p = 0.0315), respectively. Increased wall stress was associated with a decreased FEV1/FVC ratio. Conclusions The severity of airflow limitation in COPD was correlated with increased LV wall stress. It is suggested that respiration in pulmonary obstruction is associated with an increased negative intrathoracic pressure when compared with normal lung function, which is transmitted to the heart and increases the transmural pressure gradient and thereby distending forces on the heart. Increased ventricular wall stress is known to be associated with a broad variety of unfavourable consequences, which should be taken into account to contribute to a worse prognosis in COPD.